2022
DOI: 10.3390/plants11131754
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Ancient Grapevine Cultivars in the Balearic Islands: Sanitary Status Evaluation and Virus Elimination

Abstract: Recuperation and genetic diversity preservation of local cultivars have acquired a huge interest in viticulture areas worldwide. In the Balearic Islands, most of the old cultivars are only preserved in grapevine germplasm banks, and so far, the sanitary status of these local cultivars has remained unexplored. The aim of this study was to survey and detect the virus incidence of all conserved cultivars in the government Grapevine Germplasm Bank of the Balearic Islands and to promote the sanitary recovery of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition to this, grapevine biodiversity is currently facing significant threats and undergoing a widespread contraction, partly due to the “globalization of wine” phenomenon [ 69 ]. This trend has resulted in the global cultivation of a limited number of popular grape cultivars, such as Cabernet Sauvignon, Merlot, and Chardonnay [ 70 ]. Ampelographic collections like the D2 vineyard play a crucial role in preserving grapevine biodiversity and serve as valuable genetic resources [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, grapevine biodiversity is currently facing significant threats and undergoing a widespread contraction, partly due to the “globalization of wine” phenomenon [ 69 ]. This trend has resulted in the global cultivation of a limited number of popular grape cultivars, such as Cabernet Sauvignon, Merlot, and Chardonnay [ 70 ]. Ampelographic collections like the D2 vineyard play a crucial role in preserving grapevine biodiversity and serve as valuable genetic resources [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the emerging need to identify genetic material with high fruit quality and unique wine characteristics has intensified the conservation of ancient grapevine genetic material and indigenous cultivars, not only in gene bank collections but also in field collections. In several cases, special care was taken in relation to their sanitary status [ 3 , 4 , 5 , 6 ]. In Greece, during the period 1960–1980, intense cultivation of only specific Greek cultivars and the dominant foreign ones resulted in a drastic limitation of the cultivation and under-utilization of the many autochthonous cultivars, leading to significant genetic erosion of biodiversity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, during the period 1960–1980, intense cultivation of only specific Greek cultivars and the dominant foreign ones resulted in a drastic limitation of the cultivation and under-utilization of the many autochthonous cultivars, leading to significant genetic erosion of biodiversity [ 7 ]. In recent years, however, a plethora of research projects have been conducted worldwide to explore and re-utilize the biodiversity of the grapevine autochthonous cultivars [ 3 , 4 , 5 , 6 ]. Moreover, maintaining a wide range of cultivars is of fundamental importance for identifying and preserving the most adequate plant genetic material with resilience to specific environmental stressors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of virus accumulation in the grapevine germplasm collections is being studied worldwide. For example, screening of autochthonous cultivars from the Balearic Islands (Spain) has shown that more than 52% of the grapevines are affected by a mixed viral infection, with the economically significant GLRaV-3 and GFLV being some of the most common viruses [19]. A metaviromic study of betaflexiviruses in the South African ampelographic collection has also revealed a predominance of multiple virus infections, including economically significant viruses [20].…”
Section: Introductionmentioning
confidence: 99%